Peningkatan Kompetensi Guru dalam Menyusun Tujuan Pembelajaran dan Alur Tujuan Pembelajaran Melalui Pendekatan Supervisi Akademik Kepala Sekolah di SMPN Satu Atap 3 Jerebuu - Dorothea Titu (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to enhance the understanding and capabilities of teachers at SMPN Satu Atap 3 Jerebuu in implementing the Merdeka Curriculum, focusing on analyzing Capaian Pembelajaran (CP) into Tujuan Pembelajaran (TP), developing Alur Tujuan Pembelajaran (ATP), and establishing Kriteria Ketuntasan Tujuan Pembelajaran (KKTP). The method used is action research (PTS) with a cyclical approach consisting of planning, implementation, observation, and reflection. In the pre-cycle phase, it was found that teachers' understanding of the Merdeka Curriculum was still low, with an average questionnaire score of 2.0. The implementation of cycle 1 showed an improvement in understanding, but challenges in applying teaching practices remained. Subsequently, cycle 2 demonstrated significant progress, with the average questionnaire score increasing to 4.0, and teachers showed improved abilities in analyzing CP, developing ATP, and using more effective Kriteria Ketuntasan. Observations and interviews during cycle 2 revealed that teachers began to implement differentiated learning and project-based approaches more effectively, although challenges still needed to be addressed. This study recommends further training, practical support, and increased resources to better support the implementation of the Merdeka Curriculum in schools.